1993
DOI: 10.1093/clinids/17.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Treatment of Traveler's Diarrhea with Norfloxacin: A Double-Blind, Placebo-Controlled Study During Two Seasons

Abstract: Clinical efficacy of norfloxacin for treatment of traveler's diarrhea in 106 Finnish tourists vacationing in Morocco was evaluated during two different seasons. When the criteria for diagnosis of traveler's diarrhea were fulfilled, norfloxacin (400 mg) or a placebo was given orally, twice daily for 3 days. All symptoms and signs subsided sooner in the norfloxacin group. The clearest difference was observed in the duration of diarrhea: 1.2 days in the norfloxacin group vs. 3.3 days in the placebo group (P < .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Anti-bacterial drugs have been shown to reduce initiation of therapy until the last unformed stool is passed in cases of TD by 1-3 days compared with no therapy or placebo (118)(119)(120)(121), and combination of an antibiotic with loperamide further shortens duration of illness ( 111 ). Fluoroquinolones such as ciprofl oxacin or levofl oxacin have been the primary anti biotics of choice for most destinations ( 119,120,122 ), although growing resistance to this class of antibiotics may change this (123)(124)(125). In addition, there is evidence that most Campylobacter are fl uoroquinolone resistant and the use of macrolides such as azithromycin for treatment is recommended ( 126 ).…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-bacterial drugs have been shown to reduce initiation of therapy until the last unformed stool is passed in cases of TD by 1-3 days compared with no therapy or placebo (118)(119)(120)(121), and combination of an antibiotic with loperamide further shortens duration of illness ( 111 ). Fluoroquinolones such as ciprofl oxacin or levofl oxacin have been the primary anti biotics of choice for most destinations ( 119,120,122 ), although growing resistance to this class of antibiotics may change this (123)(124)(125). In addition, there is evidence that most Campylobacter are fl uoroquinolone resistant and the use of macrolides such as azithromycin for treatment is recommended ( 126 ).…”
Section: Recommendationmentioning
confidence: 99%
“…A review of nine randomized clinical trials and one Cochrane review assessing fl uoroquinolone use for the treatment of TD ( 116,119,122,(128)(129)(130)(131) found overall reductions in diarrhea duration compared with placebo and evidence from these studies showed no serious harm associated with fl uoroquinolone use; however, the literature on the use of fl ouroquinolones in all settings has demonstrated risks of development of Clostridium diffi cile infection and risks for tendonopathies and arthropathies ( 132 ). For all antibiotics, either single-dose therapy or treatment for up to 3 days is usually suffi cient to allow resolution of symptoms.…”
Section: Non-antibiotic Therapiesmentioning
confidence: 99%
“…However, if diarrhoea is frequent and/or bloody, or high fever is present, treatment with antimicrobial agents is indicated. Erythromycin is still the drug of choice [11] but nowadays fluoroquinolones are considered to be a good, safe but expensive alternative for the treatment of human campylobacter enteritis [12]. However, Endtz and colleagues [13] reported an increase of quinolone resistance amongst campylobacter strains isolated from human stools and poultry products in the Netherlands between 1982 and 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Either alone or in combination with loperamide, they have been shown to reduce the duration of diarrhea by more than 50% compared to placebo (48,51,113,157,165). Not only are they safe and well tolerated fluoroquinolones maintain high concentrations in the stool, which may theoretically limit invasive disease.…”
Section: Antimicrobial Therapymentioning
confidence: 99%